Enhancing the Ease of Doing Business in APEC Countries: A Comprehensive Review of Literature - Canare, Tristan A (Archīum Ateneo, 2015)
Since 2006, the World Bank has been ranking almost 200 countries in terms of their business environment and the “ease of doing business” in these economies. The rationale behind this is the importance of a thriving private sector in promoting high and inclusive growth and development. It is argued that the easier it is to establish and run a business, the more investors will be encouraged to invest, and thus more employment is generated. A good business environment also promotes competition and encourages innovation and expansion (World Bank 2013). The Asia-Pacific Economic Cooperation (APEC) also has its own specialized group monitoring the progress of its members in enhancing the ease of doing business. In its 2015 edition (which looks at data from 2014), the World Bank ranked the Philippines 95th in its Doing Business Report. This is a 13-place improvement from its 2014 rank and a 38-notch jump from 2013. These improvements reflect the efforts made by key government agencies in the past years. This rise in ranking can be seen not only as an enhancement of the country’s economic fundamentals and potential for growth; it also sends out a positive signal to foreign investors, governments, institutions, and media. This paper will provide inputs to the APEC Ease of Doing Business (EoDB) Initiative which establishes the goal of an APEC-wide improvement of 25% by 2015 in the following five key areas of doing business: (1) starting a business; (2) dealing with permits; (3) getting credit; (4) trading across borders; and (5) enforcing contracts, with an interim target of 5% percent improvement by 2011.